The Middle Rectal Artery: Revisited Anatomy and Surgical Implications of a Neglected Blood Vessel. Issue 3 (11th January 2023) - Heinze, Tillmann; Fletcher, Jordan; Miskovic, Danilo; Stelzner, Sigmar; Bayer, Andreas; Wedel, Thilo
Abstract : BACKGROUND: Although the middle rectal artery is a relevant anatomical landmark for rectal resection and lateral lymph node dissection, descriptions of this entity are highly divergent. OBJECTIVE: Dissection, visualization, morphometry, and 3-dimensional reconstruction of the middle rectal artery to facilitate its management in surgery. DESIGN: Macroscopic dissection, histologic study, morphometric measurements, and virtual modeling. SETTING: University laboratory of applied surgical anatomy. PATIENTS: This study includes formalin-fixed hemipelvis specimens (n=37) obtained from body donors (age, 67–97 y). MAIN OUTCOME MEASURES: The main outcome measures are photo documentation of origin, trajectory, diameter, and branching pattern; immunolabeling of lymphatics; and 3-dimensional reconstruction of the middle rectal artery. RESULTS: The middle rectal artery was present in 71.4% of body donors (21.4% bilateral, 50% unilateral), originated from the anterior division of the internal iliac artery, and branched either from the internal pudendal artery (45.5%), the inferior gluteal artery (22.7%), the gluteal-pudendal trunk (22.7%), or a trifurcation (9.1%). One to 3 branches of varying diameters (0.5–3.5 mm) entered the mesorectum from the ventrolateral (35.7%), lateral (42.9%), or dorsolateral (21.4%) aspect. The middle rectal artery was accompanied by podoplanin-immunoreactive lymphatic vessels and gave off additional branches (81.8%) to the urogenital pelvic organs. Three-dimensional reconstruction revealed the complex course of the middle rectal artery from the pelvic sidewall through the pelvic nerve plexus and parietal pelvic fascia into the mesorectum. LIMITATIONS: Findings retrieved from body donors may be prone to age- and fixation-related processes. CONCLUSIONS: The investigation disclosed the rather high prevalence of the middle rectal artery, its 3-dimensional topographic anatomy, and its proximity to the autonomic pelvic nerves. These features play a role in the surgical management of this blood vessel. The data provide the anatomical rationale for the lateral lymphatic spread of rectal cancer and an anatomical basis for nerve-preserving lateral lymph node dissection.